Cost-effectiveness of perioperative durvalumab plus FLOT for resectable gastric and gastroesophageal junction adenocarcinoma in the United States - Zhang, Jiahao; You, Caicong; Fu, Wu; Zheng, Liushi; Liu, Maobai; Li, Na (Frontiers in Immunology, 2026)
ObjectiveThis study evaluated the cost-effectiveness of perioperative durvalumab plus FLOT compared with FLOT alone in patients with resectable gastric and gastroesophageal junction (G/GEJ) adenocarcinoma in the United States.MethodsWe developed a semi-Markov model to evaluate the cost-effectiveness of perioperative durvalumab plus FLOT compared with FLOT alone from the perspective of U.S. healthcare payers. The model utilized a 10-year time horizon with a 4-week cycle length. Clinical efficacy and safety data were primarily derived from the phase III MATTERHORN trial, while transition probabilities for subsequent lines of therapy were extrapolated from the RAINBOW trial. Direct medical costs were estimated using 2025 pricing data from CMS fee schedules and published literature. Health utility values were obtained from previous studies. Both costs and outcomes were discounted at an annual rate of 3%. Deterministic and probabilistic sensitivity analyses were performed to assess the robustness of the results.ResultsCompared with perioperative FLOT alone, the addition of durvalumab provided an additional 0.84 QALY, with an incremental cost of $104,256.12, yielding an ICER of $124,661.87 per QALY gained. Sensitivity analyses indicated that the cost of durvalumab and the utility associated with event-free survival (EFS) were the key drivers of model uncertainty.ConclusionFrom the perspective of U.S. healthcare payers, perioperative durvalumab plus FLOT is a cost-effective strategy compared with FLOT alone for patients with resectable G/GEJ adenocarcinoma.